2020
DOI: 10.2147/ott.s249906
|View full text |Cite
|
Sign up to set email alerts
|

<p>Methylcrotonoyl-CoA Carboxylase 2 Promotes Proliferation, Migration and Invasion and Inhibits Apoptosis of Prostate Cancer Cells Through Regulating GLUD1-P38 MAPK Signaling Pathway</p>

Abstract: Prostate cancer (PCa) is the most common cancer in American men, and the mechanisms of development and progression are still not completely clear. Methylcrotonoyl-CoA carboxylase 2 (MCCC2) was previously identified overexpressed in PCa with lymph node metastasis, but its specific role and mechanisms need further investigation. This study aimed to investigate the role of MCCC2 in PCa cells and its underlying mechanisms. Materials and Methods: Quantitative RT-PCR and Western blotting were used to detect MCCC2 mR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 40 publications
2
16
0
Order By: Relevance
“…Even though the number of analyzed tumor samples is limited, these results suggest that leucine can be a metabolic substrate for brain tumor cells. The expression of the MCC has also been confirmed previously in various breast [30], prostate [29,63], colorectal [31], and hepatocellular [32] tumors. Furthermore, several studies revealed novel signaling and regulatory functions intervened by the smaller subunit of MCC, MCCC2, in cancer cells [29,32].…”
Section: Discussionsupporting
confidence: 70%
See 3 more Smart Citations
“…Even though the number of analyzed tumor samples is limited, these results suggest that leucine can be a metabolic substrate for brain tumor cells. The expression of the MCC has also been confirmed previously in various breast [30], prostate [29,63], colorectal [31], and hepatocellular [32] tumors. Furthermore, several studies revealed novel signaling and regulatory functions intervened by the smaller subunit of MCC, MCCC2, in cancer cells [29,32].…”
Section: Discussionsupporting
confidence: 70%
“…The expression of the MCC has also been confirmed previously in various breast [30], prostate [29,63], colorectal [31], and hepatocellular [32] tumors. Furthermore, several studies revealed novel signaling and regulatory functions intervened by the smaller subunit of MCC, MCCC2, in cancer cells [29,32]. In this respect, MCCC2 can affect the intracellular signaling cascade facilitated by promoting the activation of ERK in the cytosol of human hepatocarcinoma cells [32] or regulating the GLUD1-P38 MAPK signaling pathway in [29] prostate cancer cells.…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…For example, the high expression of MCCC2 predicts a poor prognosis and can promote cell proliferation in colorectal and breast cancer [ 19 , 22 ]. The oncogenic role of MCCC2 is partially involved in the GLUD1-P38 MAPK signaling pathway [ 23 ]. However, it is currently unclear whether MCCC2 also plays an important role in the progression of HCC and the effect of MCCC2 on leucine metabolism has yet not been deciphered.…”
Section: Introductionmentioning
confidence: 99%